ISOLATION OF ANTIOXIDANT COMPOUNDS FROM KEBIUL (CAESALPINIA BONDUC L) SEED SHELLS - Mohd Abdus salam; Indah Permata Yuda; Juniarti (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2026)
Caesalpinia bonduc L. is a medicinal plant widely distributed in tropical and subtropical regions and has long been utilized in traditional medicine for the treatment of various ailments. Its seeds are recognized as a rich source of bioactive secondary metabolites, particularly flavonoids, phenolic compounds, terpenoids, and diterpenes, which have been associated with antioxidant, anti-inflammatory, antimicrobial, and antidiabetic activities. However, studies focusing on the isolation, purification, and characterization of individual bioactive compounds from C. bonduc seeds remain limited. Therefore, this study aimed to isolate, purify, identify, and evaluate the antioxidant activity of bioactive compounds obtained from C. bonduc L. seeds. Bioactive compounds were isolated from the seed extract through successive extraction, chromatographic separation, and purification procedures. The purified compound was subsequently characterized by phytochemical identification and evaluated for its free radical scavenging activity using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. The isolated compound was identified as a flavonoid based on its chemical characteristics. Antioxidant evaluation demonstrated that the isolated flavonoid exhibited potent free radical scavenging activity, with a half-maximal inhibitory concentration (IC₅₀) of 3.31 ± 0.12 µg/mL, indicating a very strong antioxidant capacity. The findings demonstrate that C. bonduc seeds constitute a valuable source of naturally occurring antioxidant compounds and support their traditional medicinal use.